2014
DOI: 10.1159/000364949
|View full text |Cite
|
Sign up to set email alerts
|

Response to Chemotherapy, Reexposure to Crizotinib and Treatment with a Novel ALK Inhibitor in a Patient with Acquired Crizotinib Resistance

Abstract: The treatment of advanced non-small cell lung cancer (NSCLC) has dramatically changed over the last decade. It has developed from an unspecific approach based on platinum doublet chemotherapy to a personalized, molecularly targeted therapy. Crizotinib is a new tyrosine kinase inhibitor approved for the treatment of NSCLC with gene rearrangement of EML4 and ALK. Despite good initial responses, patients treated with crizotinib relapse after an average of 10 months. In this case report, we present a patient with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 11 publications
0
10
0
Order By: Relevance
“…In lung cancer, EML4-ALK copy-number gain and increased expression are reported in association with crizotinib resistance (18, 19). There are recent case reports of ALK+ NSCLC patients who became refractory to crizotinib obtaining secondary responses upon re-challenge after a period off the drug (45, 46). Both patients, however, received chemotherapy upon initial crizotinib discontinuation, so we do not know if ALK overdose was present or might have led to spontaneous regressions if they had been observed without therapy.…”
Section: Discussionmentioning
confidence: 99%
“…In lung cancer, EML4-ALK copy-number gain and increased expression are reported in association with crizotinib resistance (18, 19). There are recent case reports of ALK+ NSCLC patients who became refractory to crizotinib obtaining secondary responses upon re-challenge after a period off the drug (45, 46). Both patients, however, received chemotherapy upon initial crizotinib discontinuation, so we do not know if ALK overdose was present or might have led to spontaneous regressions if they had been observed without therapy.…”
Section: Discussionmentioning
confidence: 99%
“…Also, patients with acquired EGFR T790M resistance mutations who are taken off drug demonstrate loss of this mutation in their tumors, which may explain why these patients respond upon retreatment with EGFR inhibitors that do not target the T790M mutation . Similar retreatment effects are also seen with crizotinib . Such findings must be interpreted carefully, as drug holidays prior to the acquisition of resistance may actually speed the resistance process ; however, in total, these results suggest the optimization of dosing regimens for oncogene‐targeted therapeutics is never ‘one size fits all.’ Optimal dosing schedules should be actively explored in preclinical models and inform the clinical testing of distinct dosing hypotheses in patients.…”
Section: A Road Map For Targeting Oncogene Addictionmentioning
confidence: 94%
“…However, two case reports have shown that patients may respond positively to rechallenge with crizotinib, lending support to the clinical investigation of discontinuous dosing with ALK TKIs. 74 , 75 …”
Section: Intermittent Dosingmentioning
confidence: 99%